2003
DOI: 10.1074/jbc.m211278200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-dependent Protein Kinase II Regulation of c-FLIP Expression and Phosphorylation in Modulation of Fas-mediated Signaling in Malignant Glioma Cells

Abstract: (5, 6). FADD has a carboxylterminal DD and an amino-terminal death effector domain (DED). Through its DED, FADD recruits the DED-containing apoptosis-initiating proteases caspase-8 (7, 8) and caspase-10 (9 -11) to the Fas receptor to assemble a DISC (12). In the DISC, caspase-8 is cleaved through autoproteolysis of caspase-8 molecules in close proximity (13). Active caspase-8 subunits are released into the cytoplasm to cleave downstream effector caspases such as caspase-3 (14), which subsequently cleaves its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 53 publications
4
60
0
Order By: Relevance
“…Treating resistant cells with the CaMK II inhibitor KN-93 inhibited CaMK II activity, reduced c-FLIP expression, inhibited c-FLIP phosphorylation, and rescued Fas agonistic antibody (CH-11) sensitivity [19,71]. Targeting this pathway may provide novel therapeutic strategies in treating cancers with upregulated CaMK II.…”
Section: C-flip Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating resistant cells with the CaMK II inhibitor KN-93 inhibited CaMK II activity, reduced c-FLIP expression, inhibited c-FLIP phosphorylation, and rescued Fas agonistic antibody (CH-11) sensitivity [19,71]. Targeting this pathway may provide novel therapeutic strategies in treating cancers with upregulated CaMK II.…”
Section: C-flip Functionmentioning
confidence: 99%
“…Targeting this pathway may provide novel therapeutic strategies in treating cancers with upregulated CaMK II. Interestingly, phosphorylation of c-FLIP variants by CaMK II appears to promote c-FLIP L recruitment to the DISC and inhibit TRAIL-induced apoptosis [19,71], but phosphorylation of c-FLIP L by protein kinase C or the bile acid glycochenodeoxycholate results in decreased c-FLIP L recruitment to the DISC and increased sensitivity of hepatocellular carcinoma cells to TRAIL-triggered apoptosis [72]. Thus, the particular site of phosphorylation in c-FLIP L appears to influence the functional outcome of this protein on apoptosis.…”
Section: C-flip Functionmentioning
confidence: 99%
“…Phosphorylation of FADD can enhance apoptosis induced by etoposide (37). Also, PKC II may regulate cellular FLIP expression and phosphorylation in response to Fas (38). It is conceivable that 5/6-kinase could selectively phosphorylate a component within DISC and alter its function specific to TNF␣ signaling.…”
Section: /6-kinase Inhibits Tnf-induced Apoptosismentioning
confidence: 99%
“…Although others did not identify individual phosphorylation sites, they suggested that CaMKII phosphorylates c-FLIP L on threonine, [20][21][22] and that phosphorylation is involved in the detachment of c-FLIP from the TRAIL DISC. 32 However, because CaMKII inhibition did not affect S193 phosphorylation (data not shown), CaMKII is unlikely to be involved in S193 phosphorylation.…”
Section: Phosphorylation Of C-flip By Pkcmentioning
confidence: 99%
“…Although we showed earlier that the levels of c-FLIP are determined by ubiquitylation, others have reported that c-FLIP is modulated by phosphorylation. [19][20][21][22] Hence, we studied how these posttranslational modifications regulate c-FLIP in concert.…”
mentioning
confidence: 99%